Evaluation of The Implementation of Sport Tourism Events in Bukit Lawang Orangutan Trail Activities (BLOT 2024) - Purba, Joen Parningotan; br Payung , Milda Vinna; Pratiwi, Endang; Manalu, Riski Bastanta B (Halaman Olahraga Nusantara : Jurnal Ilmu Keolahragaan, 2025)
BLOT 2024 is not just a sports event, but also a momentum for nature conservation, local economic empowerment, and strengthening the branding of Bukit Lawang as an international trail destination. The combination of Leuser's natural trajectory, government support, strategic partnerships, and environmental and social aspects make this event really useful and has a positive impact. BLOT is not just a running race. It is designed as a tangible form of synergy between nature conservation, sports, and local tourism development. Runners are not only challenged to conquer extreme terrain with uphill, downhill, river and wilderness trails, but are also invited to interact directly with the natural wilderness, including the protected habitat of Sumatran orangutans. This activity aims to: 1) Promote sports tourism in Langkat Regency. 2) Increase awareness of environmental conservation, especially the ecosystem of Gunung Leuser National Park. 3) Encourage local economic empowerment through the participation of MSMEs and the tourism sector. 4) Make Bukit Lawang an international standard trail running destination. By integrating scientific data, field practice, and traveler input, BLOT can further uphold sustainable and responsible sport tourism, while maintaining the reputation and sustainability of Bukit Lawang as a leading destination